2022
DOI: 10.1080/14660970.2022.2059872
|View full text |Cite
|
Sign up to set email alerts
|

Social media marketing strategy in English football clubs

Abstract: The aim of this study is to explore the evolving social media marketing strategies of football clubs involved in the English Premier League (EPL), in a constantly changing sporting and digital landscape. Interviews conducted with practitioners from a range of clubs revealed that social media marketing has been fully adopted as a key strategic marketing channel. Other insights include the importance of trust to clubs being able to harness the collective of passionate fans on social media platforms. Also, how cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…The use of social media then spreads to more people as a result of this. McCarthy et al (2022) further state that fan research has shown the significance of fans using social media for (a) a sense of community and belonging; (b) information and entertainment related to the football team they support; (c) respect through their influence among the fan base; (d) based on trust, the expression and nurturing of their emotional connection and passion for the club they support; and, (e) positive and negative reactions to the club.…”
Section: Social Media Marketingmentioning
confidence: 90%
“…The use of social media then spreads to more people as a result of this. McCarthy et al (2022) further state that fan research has shown the significance of fans using social media for (a) a sense of community and belonging; (b) information and entertainment related to the football team they support; (c) respect through their influence among the fan base; (d) based on trust, the expression and nurturing of their emotional connection and passion for the club they support; and, (e) positive and negative reactions to the club.…”
Section: Social Media Marketingmentioning
confidence: 90%
“…Following the topic of social networks as marketing communication tools, McCarthy et al (2022) describe these as strategically important. Via them, a sports organization can ensure the achievement of goals.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship marketing and fan engagement in football Social media have become indispensable to football teams' communication and marketing strategies (Guzm an et al, 2021;McCarthy et al, 2022). This significance is further magnified as consumers assume more active roles (Kolyperas et al, 2019).…”
Section: Social Media Engagement In Football Leaguesmentioning
confidence: 99%
“…While the existing literature is prolific regarding the use of social media by sports clubs or athletes (e.g. Anagnostopoulos et al, 2018;McCarthy et al, 2022;Zakerian et al, 2022), there exists a gap specific to how football leagues employ these digital channels. This study addresses this gap by adding an international perspective, analyzing the social media accounts of leagues from different geographic areas (Europe, North America, and South America).…”
Section: Social Media Engagement In Football Leaguesmentioning
confidence: 99%